Effects of restoration duration on plant community and soil chemical stoichiometry characteristics in mine waste dumps - Shao, Yazhou; Zuo, Hejun; Ma, Yunxia; Ma, Xiaolu; Li, Gangtie (Frontiers in Plant Science, 2025)
Taking the dump slopes and platforms with different restoration years (2Y, 6Y, 10Y, 12Y) in Manlailiang Open-pit Coal Mine as the research objects, combined with the unmined original landform (CK), the effects of restoration years on plant communities and soil stoichiometric characteristics were explored. The vegetation characteristics were investigated by ‘ large quadrat nested small quadrat ‘, and the soil nutrients and stoichiometric ratio were measured in 0–30 cm soil layer, combined with statistical methods such as two-factor analysis of variance. With the increase of restoration years, the species increased, the importance value of Medicago sativa decreased, and the native perennial plants became the dominant species (shady slope was better than sunny slope). Organic carbon increased, nitrogen showed ‘ V ‘ shape (12Y super CK), and phosphorus was stable; the topographic measurement of 12Y is close to CK, and the vegetation and soil are synergistically close to CK. The restoration is divided into three stages (initial 2Y-6Y, middle 10Y, late 12Y), 12Y near-natural state (as a key node), and the shady slope recovery is the best, which can provide a basis for differentiated restoration.